2016
DOI: 10.3390/f7100236
|View full text |Cite
|
Sign up to set email alerts
|

The Dynamic Trend of Soil Water Content in Artificial Forests on the Loess Plateau, China

Abstract: Extensive vegetation restoration projects have been widely implemented on the Loess Plateau, China, since 1998. In addition, increasing attention has been paid to the influence of revegetation on soil water. However, the response of the soil water content (SWC) to vegetation construction and management has not been adequately studied. In this study, three types of typical artificial vegetation on level bench land were selected, including Pinus tabulaeformis Carr., Prunus sibirica L., and Hippophae rhamnoides L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 44 publications
1
4
0
Order By: Relevance
“…The results of this study indicate that the average SMC of R. pseudoacacia forestland was 11.54 ± 0.36% (Table 3), which is similar to the results found by Chang [35] and Hou [36]. Previous studies indicated that the SMC is a limiting factor that affects the normal growth of R. pseudoacacia on the Loess Plateau [3,9]. Our results also suggest that there is a significant relationship between the SMC and stand density distribution, with a correlation coefficient of 0.243 ** (Table 4).…”
Section: Effects Of Smc Ser and Soil Nutrients On Stand Densitysupporting
confidence: 88%
See 2 more Smart Citations
“…The results of this study indicate that the average SMC of R. pseudoacacia forestland was 11.54 ± 0.36% (Table 3), which is similar to the results found by Chang [35] and Hou [36]. Previous studies indicated that the SMC is a limiting factor that affects the normal growth of R. pseudoacacia on the Loess Plateau [3,9]. Our results also suggest that there is a significant relationship between the SMC and stand density distribution, with a correlation coefficient of 0.243 ** (Table 4).…”
Section: Effects Of Smc Ser and Soil Nutrients On Stand Densitysupporting
confidence: 88%
“…where Q represents the sap flow (cm 3 ), J s represents the sap flow density (cm 3 •cm -2 •h -1 ), As represents the sapwood area (cm 2 ), t is the time that the sap flow density was recorded, K is a dimensionless variable, d T is the temperature difference value associated with the thermal diffusion probe, and d TM is the maximum temperature difference value when the velocity of the sap flow is zero. An overall situation trend analysis was carried out using ArcGIS 10.1 (Environmental Systems Research Institute, Inc., Redlands, CA, USA).…”
Section: ×100%mentioning
confidence: 99%
See 1 more Smart Citation
“…However, the deep loess layer stores and regulates water [8]. Therefore, research on the relationship between vegetation growth and soil moisture in this area has been of great interest [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Given its white or pinkish flowers in spring, ripe yellow fruit in summer, and highly diverse leaf colors in autumn, the tree is considered to have particular ornamental value 2 , 3 . As a pioneer tree species in the restoration of vegetation, P. sibirica can tolerate cold, drought, and barren land and, thus, has high ecological value 1 , 4 . In addition, the seeds of this species contain amygdalin and high-quality oils, which have significant economic value 5 , 6 .…”
Section: Introductionmentioning
confidence: 99%